Effects of the surface roughness on heat transfer of perpendicularly impinging co-axial jet - Celik, Nevin (Springer, 2011)
Current work presents the comparison of the cooling characteristics of roughened and smooth heated surfaces subjected to co-axial impinging jet. The work fluid is air and the data runs are performed for jet Reynolds numbers for 10,000, 20,000 and 40,000, and non-dimensional surface to jet exit spacing, H/D, from 1 to 10. The co-axial jet configuration is based on a fully developed pipe flow encountering a double-pipe arrangement and splitting between the two pipes. The inner to outer diameter ratio is 0.5. A straight pipe without inner section is used as the circular jet. The impingement of circular jets to the roughened and smooth surfaces is also performed for comparison. Average Nusslet numbers were obtained to show the heat transfer enhancement from the surface. A good agreement between the literature and present paper was obtained. As a result, average Nusselt number with coaxial jet impingement to the roughened surface increased by up to 27% comparing to the circular jet impingement. In addition, the average Nusselt number increased with roughened surface by up to 6% over the whole surface area, comparing to the smooth surface.
Keywords: Impingement; Channels; Smooth; Gas